COMMUNICATION OF PUBLIC POLICY IN HANDLING PROBLEMS OF PTPN II (PERSERO) EX-HGU LAND IN NORTH SUMATRA - Lubis, Afifi; Sinaga, Nelly Azwarni; Sazali, Hasan (Sosiohumaniora, 2024)
This research analyzes how communication between stakeholders is established in implementing policies for handling land issues in the former PTPN II HGU in North Sumatra. The research method uses a qualitative descriptive approach by tracing related Literature studies. The research results show that the media and communication carried out by the North Sumatra Provincial Government in handling land issues of the former PTPN II HGU is direct communication in the form of socialization and coordination in strategic and technical forms. The communication carried out by the North Sumatra BPN Regional Office is direct in the form of support to the North Sumatra Provincial Government. The BPN Regional Office plays a vital role because regulations related to HGU come from BPN RI. The policy public communication strategy is carried out by increasing the intensity of public policy communication, involving the public in policy-making, and conveying information through the media. Factors influencing policy include openness of information, credibility, and government authority in reducing uncertainty and risk in resolving former PTPN II HGU problems. This research provides insight into alternative policy models for the North Sumatra Provincial Government in handling land conflicts. This research helps to understand the typology of land conflicts handled by BPN RI. This also emphasizes the need to increase legal awareness among the community and overcome systematic acts of provocation that lead to conflicts over land rights in North Sumatra Province.